Pre-clinical and post-clinical process of committing to e-psychiatric treatment—an evaluation of patient perspective with emphasis on designing cost-effective longitudinal treatment - Sendler, Damian Jacob; Pardo, Dayra (mHealth, 2019)
Background: e-Health is a branch of medicine, specializing in providing cost-effective care, using computer-based technologies. This study evaluates the patient-centered perspective on the process of committing to e-based therapies, emphasizing pre-clinical contemplation stage and post-clinical commitment to treatment stage. Methods: We set up an online focus group. Participants (15 M, 15 F) were recruited through postings on health sites promoting e-health solutions. Each participant received login information and was asked to participate in a two-hour, moderated and recorded conversation with the principal investigator about the use of e-health solutions. Results: The results stratify data into two stages of acquisition and processing information about e-health solutions: pre-clinical and clinical. In the pre-clinical stage, most patients are health information seekers, meaning that they seek to learn about e-psychiatric solutions as much as possible, comparing different treatment modalities. To accomplish this, they research health sites, discussion forums, and read review notes to evaluate the best course of action; Patients prioritize finding an easy and affordable solution that offers access to the qualified provider without the hassle of attending treatment in person. In clinical stage, patients devote time to understanding their interaction with the provider—they look whether the doctor is flexible in offering blended therapeutic approach; they will often tell the physician that they are concerned with cost of treatment, and believe that e-health solutions give them access to a dedicated provider when needed, which lowers the overhead cost of treatment. Once the patient is comfortable with his treatment planning, they establish commitment toward extended psychiatric care. Conclusions: This study evaluated how patients decide on what providers to access when seeking e-psychiatric health solutions. We show that the cost of treatment and the provider’s commitment to cost-effective, flexible e-health follow-ups predicts the patient’s success of remaining in treatment long-term.